2022
DOI: 10.1103/physrevlett.129.118001
|View full text |Cite
|
Sign up to set email alerts
|

Active Nematic Flows over Curved Surfaces

Abstract: Cell monolayers are a central model system to tissue biophysics. In vivo, epithelial tissues are curved on the scale of microns, and curvature's role in the onset of spontaneous tissue flows is still not well-understood. Here, we present a hydrodynamic theory for an apical-basal asymmetric active nematic gel on a curved strip. We show that surface curvature qualitatively changes monolayer motion compared to flat space: the resulting flows can be thresholdless, and the transition to motion may change from conti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
(42 reference statements)
0
11
0
1
Order By: Relevance
“…Our findings and the generic minimal model of single-cell curvotaxis could also provide insights into the orientation and migration of cells in aggregates such as confluent cell monolayers on curved surfaces [44][45][46][47] . The competitions among cell-cell junction, cortical actin bending, and cell contractility could result in even richer emergent collective behaviors 44 .…”
Section: Implications To Curvotaxis On More Complex Curved Surfacesmentioning
confidence: 71%
See 1 more Smart Citation
“…Our findings and the generic minimal model of single-cell curvotaxis could also provide insights into the orientation and migration of cells in aggregates such as confluent cell monolayers on curved surfaces [44][45][46][47] . The competitions among cell-cell junction, cortical actin bending, and cell contractility could result in even richer emergent collective behaviors 44 .…”
Section: Implications To Curvotaxis On More Complex Curved Surfacesmentioning
confidence: 71%
“…Our findings and the generic minimal model of single-cell curvotaxis could also provide insights into the orientation and migration of cells in aggregates such as confluent cell monolayers on curved surfaces [44][45][46][47] . The competitions among cell-cell junction, cortical actin bending, and cell contractility could result in even richer emergent collective behaviors 44 . Particularly, based on our single-cell models, for confluent cell monolayers on microcylinders, the cell-cell interactions may be modeled as nematic interactions in analogous to those in liquid crystals 48 .…”
Section: Implications To Curvotaxis On More Complex Curved Surfacesmentioning
confidence: 71%
“…Notably, past studies have suggested that the orientation of epithelial cells changes along with the geometry of the 3D curved surface and that a geometry-driven flow can occur. 29 Since the buckled 3D gel can also provide suitable geometric confinement in the height direction, the analysis of collective motion on the 3D buckled gel surface remains a future challenge. In addition, unlike the PDMS elastomers used in previous studies, hydrogels can be stretched and contracted to provide mechanical stimulation to epithelial cell populations, making it possible to validate mechanical response stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…But biological environments such as the gut are highly curved. To study the impact of curvature on tissue dynamics, Samuel Bell of the Curie Institute in Paris and colleagues developed a hydrodynamic theory that works for bumpy surfaces and shows that tissue movement in a corrugation substantially differs from that along a flat surface [1]. The results could have implications for models of organ morphogenesis and cancer spread.…”
mentioning
confidence: 99%
“…This model previously proved successful in describing tissue dynamics over a flat surface. The team expanded it by adding in a force field that accounts for the Credit: S. Bell et al [1] impact of curvature on how cells align with each other as they move.…”
mentioning
confidence: 99%